FAKTOR – FAKTOR YANG MEMPENGARUHI AKSEPTOR KB DALAM PENGGUNAAN ALAT KONTRASEPSI DALAM RAHIM DI PUSKESMAS SIDOMULYO - Endah Purwani Sari (STIKES HUSADA GEMILANG, 2018)
Intra Uterine Device is a device or object that is injected into the very effective uterus, reversible and long-term, and it can be used by all women of reproductive age. This study aims at seeing the factors that influence the acceptors of birth control in the use of Intra Uterine Device in Sidomulyo Health Center, Pekanbaru Riau in 2015. This research is descriptive analytics and cross sectional research design. The population the research was all the acceptors of birth control who visited Sidomulyo Health Center (370 acceptors), and there was 79 respondents for the sample that caught through the accidental sampling. Data processing were analyzed over the SPSS program and data analysis was carried out in univariate, bivariate, and multivariate. The results showed that the acceptors of birth control in the age group of 20-30 years were 46.8%, the parity of acceptors of birth control in the multiparous parity were 64.6%, and knowledge of acceptors of birth control in poor category were 38.0%. The chi square test on age is p = 0,000 (p value <0.05), which means that there is a significant relationship between age of respondents and acceptors of IUD birth control, the parity of respondents is p = 0.135 (p value> 0.05) which means there is no significant relationship between the parity of respondents and the acceptors of birth control, and the knowledge of respondents is p = 0.30 (p value <0.05) which means that there is a significant relationship between the knowledge of respondents and acceptors of IUD birth control. Based on the results, it is expected that health workers, especially midwives, can advance counseling to the acceptor candidates of birth control about contraceptives, especially the IUD in Sidomulyo Health Center Pekanbaru.